PERANCANGAN VIDEO COMPANY PROFIL DI SMAN 2 TEMBILAHAN - Sandi Arjun Pratama; Samsudin Sadek; Bayu Rianto (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2022)
Currently, the media for the introduction of the SMAN 2 Tembilahan school still uses brochures, banners and the school website. The media used by this school is very expensive, especially in its production and is less popular in the community. With the creation of a video company profile based on interactive multimedia and using the multimedia development life circle (MDLC) method, the result of the concept being studied is the design of a video company profile for SMAN 2 Tembilahan and the results of this design produce storyboard results, editing design for collecting materials produces data- video data that is taken and generated at the stage of making the finished video. The results of the questionnaire of five questions that answered normally out of 6 total number of respondents there were 12% for those who answered agreed there were 32 the total number of respondents yielded a percentage of 64% and those who answered strongly agreed with 12 with a percentage of 24%. The results of the questionnaire show that the video display is very interesting and easy to understand, with this company profile video it is very helpful and improves information services in the form of videos in the community and the world of informatics. Saat ini media pengenalan sekolah SMAN 2 Tembilahan masih menggunakan brosur, spanduk dan website sekolah. Media yang digunnakan sekolah ini banyak memakan biaya apalagi dalam produksinya dan kurang diminatai di masyarakat. Dengan adanya pembuatan video company profil berbasi multimedia interaktif dan mengggunakan metoede multimedia development life circle (MDLC) hasil dari konsep yang di teliti adalaha perancangan video company profil SMAN 2 Tembilahan dan hasil dari perancangan ini menghasilkan hasil dari storyboard,desain editing pengumpulan bahan menghasilkana data-data video yang diambil dan di hasilkan di tahap pembuatan video yang sudah jadi. Hasil dari kusioner dari lima pertanyaan yang menjawab biasa aja dari 6 jumlah total keseluruhan responden ada 12% untuk yang menjawab setuju ada 32 jumlah total keseluruhan responden menghasilkan persentase 64% dan yang menjawab sangat setuju dengan jumlah 12 dengan persentase 24%. Hasil dari kuisioner nya adalah tampilan video sangat di minati dan mudah di pahami, dengan adanya video company profil ini sangat membantu dan meningkatkan layanan informasi berbentuk video di masyarakat dan dunia informatika.